Limiting Factors for a Planar Solid Oxide Fuel Cell Under Different Flow and Temperature Conditions. Issue 5 (21st June 2013) - Leone, P.; Matencio, T.; Garciä, M. E.; Domigues, Z. R.; Lanzini, A.; Santarelli, M.
Abstract The work investigates the performance of an anode supported solid oxide fuel cell under relevant conditions at different flow and temperature settings with the aim to identify performance limiting factors through impedance spectroscopy. Impedance spectroscopy is used to deconvolute impedance spectra of an in‐operating SOFC and identify limiting overpotentials. Those measurements are made under a wide range of flow and temperature conditions. In particular, oxidant flow rate is varied yielding fuel cell operation with 20, 40, 60, 80% oxidant utilization; fuel is instead changed in terms of flow and composition: fuel utilization factors in the range of 20–80% are investigated as well as the dilution with nitrogen. The operating temperature is varied in the range between 650 and 800 °C with steps of 50 °C. Results show that charge and mass transport can lead to a performance limitation according to the selected operating range for the investigated cell design. For the investigated anode‐supported design, a major improvement of performance could arise by reducing ohmic resistances (i.e. employing a thin electrolyte) and by an improvement of the anode geometry aiming at enhancing mass transport. In particular, at low temperature and high fuel utilization, fuel oxidation seems to be a relevant performance limiting factor.